Determinant Analysis of Company Debt Policy with Vector Error Correction Model Approach - Amir Hamzah; Mohamad Rizky (Global Financial Accounting Journal, 2022)
Purpose- This study uses a VECM model that aims to see the short-run and long-term effects of managerial ownership, sales growth, free cash flow, and asset structure against debt policy. Vector Error Correction Model (VECM) is a model that can be used for time series data that is not stationary but has a cointegration relationship where in the model included stationary exogenous variables as additional regressors. Research Method- The sample used in this research is quantitative data with a purposive sampling technique. Based on the criteria, the number of samples collected is 32 samples in the period 2013-2021.The data analysis techniques in this study use Vector Error Correlation Model (VECM) analysis, several stages that researchers must go through before determining the right model, namely data stationarity test, optimal lag length test, co-integration test, VAR model stability test, granger causality analysis, VAR/VECM empirical model, Impulse Response Function analysis and Variance Decomposition analysis. Findings- The results of the analysis show that in the short term only sales growth and asset structure have a significant influence on debt policy. Meanwhile, in the long-term free cash flow, asset structure and sales growth have a significant influence on debt policy, while managerial ownership has an insignificant effect on debt policy. Implication- For the company should reduce the proportion of funding from debt in the implementation of its operations so as to reduce financial distress, because funding from corporate debt causes financial distress and agency costs greater than tax savings from debt interest expense, as a result of which the company is very vulnerable to economic turmoil. For creditors who provide sources of debt funding, pay more attention to aspects of the company's asset structure to be used as collateral for debt, because the company usually uses loan funds for high-risk projects. For investors should take deeper considerations to invest in companies that have large free cash flow because companies that have large free cash flow tend to show good cash flow for the future.